Peran identitas nasional dalam membangun integrasi sosial di era modern - febriansyah, dava xavi al (Maliki Interdisciplinary Journal, 2026)
National identity plays a fundamental role in building social and national unity. In Indonesia, rich in cultural diversity, national identity serves as a key glue in maintaining harmony amidst differences. However, in the era of globalization, this identity faces significant challenges due to the influx of foreign cultures, changes in lifestyles across borders, and shifting values. This article examines how national identity is formed from a historical and social perspective, and its relevance in shaping national character. It also discusses various strategies for strengthening national identity amidst the rapid global influence, particularly through education, media, and public policies based on the values ​​of Pancasila. The success of these efforts requires synergy between the government, society, and individuals in maintaining national identity so that it remains relevant and resilient in the face of global change. With strategic and collaborative steps, national identity can continue to develop without losing the essence that shapes national character.